Analyzing E-Government Development in Kudus Local Government - Edhie Wibowo, Mr. (FIA UB, 2012)
The rise of the information society has led to major changes in citizen expectations and organizational structures, cultures and working processes. Governments will have to follow suite and adopt information society tools and working practices if they are to remain responsive to citizen needs. E-government â once a bold experiment and now an important tool for public sector transformation â has progressed to the point where it is now a force for effective governance and citizen participation, both at national and local levels. In our initial enthusiasm for e-government during the late 2002s, Indonesia tended to view e-government as a tool to improve the quality of government. Many governments in central and local levels, have been trying to utilize the advances of Information and Technology for serving the public. Some of the developments resulted as success stories, while many others resulted in failures, or not optimally utilized. Regarding the above facts, a research has been conducted in order to analyze the e-government developments in Kudus Local Government. What is the uniqueness of Kudus Local Government in developing the e-government? What are the strength and weakness within the organization, and what are the opportunity and threat outside the organization? Using qualitative analysis method in answering the questions, a field research has been done in Kudus Local Government through in-depth interviews, documents, and observations in several focuses of research, namely: leadership, human resources, organizational structure, vision and missions of organization, development control, and maintenance system. All data findings then analyzed to find the best solution for the future development of e-government. In this research, the SWOT Analysis combined with qualitative approach is used as a strategy for e-government development in the future. The result of this research shows us, that e-government development in Kudus Local Government could be improved in the future by using the precise analysis over several problems and conditions in the development process to create the best strategic plans based on the analysis . The result of this research could be used as an insight to develop a new system more effective and efficient in the future. This research also presents some suggestions for short, middle, and long-term planning for Kudus Local Government in developing e-government in the future, to shape the good governance for public service. `vga+P>secondly to analyze the utilization of the IP4Tâs results in the land management planning process in East Java.Â This research used qualitative method with descriptive approach. The conclusions obtained, Execution / implementation of IP4T in East Java Province, has been running well in quantity has been largely imposed to meet the target over the years, but planning activity from the activity IP4T land in East Java Province, it can be said the less successful as a result of these activities IP4T less fully utilized